2017
DOI: 10.1186/s12884-017-1316-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of counseling on knowledge, attitude and practice of medication use during pregnancy

Abstract: BackgroundCounseling has a significant role in improving knowledge, attitude and practice outcomes of pregnant women towards medication use. Proper counseling thus could be beneficial to prevent any medication related misadventure during pregnancy. The present study was aimed to assess the knowledge, attitude and practice (KAP) of pregnant women towards their medications, to provide counseling regarding their understanding of medication use during pregnancy and evaluate the impacts of such counseling.MethodsPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 14 publications
6
41
1
3
Order By: Relevance
“…Indeed, a key conclusion to be drawn is that the occupation, an important socio-economic indicator, significantly influenced the respondent’s knowledge since when compared with women who did not have an occupation, those from higher socio-economic strata have more adequate knowledge about the potential risks of using non-prescribed medications during pregnancy. Result of the current study is also generally consistent with a previous study identifying occupation associated with the level of knowledge [ 27 ]. Knowledge of the sample that a woman with chronic health condition should know whether or not to take a medication during pregnancy significantly varied based on their nationality.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a key conclusion to be drawn is that the occupation, an important socio-economic indicator, significantly influenced the respondent’s knowledge since when compared with women who did not have an occupation, those from higher socio-economic strata have more adequate knowledge about the potential risks of using non-prescribed medications during pregnancy. Result of the current study is also generally consistent with a previous study identifying occupation associated with the level of knowledge [ 27 ]. Knowledge of the sample that a woman with chronic health condition should know whether or not to take a medication during pregnancy significantly varied based on their nationality.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence suggests that medication counselling and appropriate risk communication could improve patient adherence to needed treatments and avert termination of wanted pregnancies [ 16 , 17 ]. It is therefore crucial for pharmacists to possess the ability to confidently and appropriately provide relevant recommendations, as well as to alleviate the concerns of pregnant drug users.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] This finding of our study further reinforces the known fact that focused and structured counseling has positive impact on knowledge and attitude of pregnant females to incorporate desirable practices during pregnancy. [ 27 ] In our study, unfavorable pregnancy outcome like abortion was found to be comparatively much higher among the pregnant females who had suboptimal BPCR index even after the counseling. This reflects the importance of BPCR to have favorable birth outcome that has been reported in previous studies too.…”
Section: Discussionmentioning
confidence: 53%